Lung deposited surface area size distributions of particulate matter in different urban areas. (July 2016) - Kuuluvainen, Heino; Rönkkö, Topi; Järvinen, Anssi; Saari, Sampo; Karjalainen, Panu; Lähde, Tero; Pirjola, Liisa; Niemi, Jarkko V.; Hillamo, Risto; Keskinen, Jorma
Abstract: Lung deposited surface area (LDSA) concentration is considered as a relevant metric for the negative health effects of aerosol particles. We report for the first time the size distributions of the LDSA measured in urban air. The measurements were carried out in the metropolitan area of Helsinki, including mobile laboratory and stationary measurements in different outdoor environments, such as traffic sites, a park area, the city center and residential areas. The main instrument in this study was an electrical low pressure impactor (ELPI), which was calibrated in the field to measure the LDSA concentration. The calibration factor was determined to be 60 μ m 2 /(cm 3 pA). In the experiments, the LDSA size distributions were found to form two modes at the traffic sites and in the city center. Both of these traffic related particle modes, the nucleation mode and the soot mode, had a clear contribution to the total LDSA concentration. The average total concentrations varied from 12 to 94 μ m 2 /cm 3, measured in the park area and at the traffic site next to a major road, respectively. The LDSA concentration was found to correlate with the mass of fine particles (PM2.5), but the relation of these two metrics varied between different environments, emphasizing the influence of traffic on the LDSA. The results of this study provide valuable information on the total concentrations and size distributions of the LDSA for epidemiological studies. The size distributions are especially important in estimating the contribution of outdoor concentrations on the concentrations inside buildings and vehicles through size-dependent penetration factors. Highlights: Lung deposited surface area (LDSA) size distributions measured in a metropolitan area. An electrical low pressure impactor (ELPI) calibrated to measure the LDSA. The LDSA was influeced by traffic more than the mass of fine particles (PM2.5). Both the nucleation and soot mode found to have a contribution to the LDSA. Size distribution data is important for the use of epidemiologial studies.